Formal vs. informal protection instruments and the strategic use of patents in an Expected-Utility framework - Peter Neuhäusler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
The present article examines the question whether or not different types of firms tend to protect their innovations with varying mechanisms. Against the background of the Expected-Utility Theory (EU-Theory), firms are differentiated by their size, technological field and their degree of internationalization. According to the EU-Theory modelling, it is hypothesized that large, high-tech and strongly internationalized firms show a stronger tendency to use formal instruments, e.g. patents, to protect their innovations, whereas small and medium-sized (SME), low-tech and weakly internationalized companies fol-low the strategy of protecting their innovations with informal instruments, e.g. secrecy, to maximize their expected utility. A twofold approach is followed to analyze the theoretical model. For the empirical testing a large-scale survey about 540 records of patenting companies in Germany is used. Differences in attitudes towards protection mechanisms and differences in the actual IPR-management behavior between firms are analyzed. The results show that the attitudes towards protecting innovative achievements only differ slightly by firm type. Large differences can be revealed on the behavioral level which, together with other findings, leads to the conclusion that mostly SMEs are forced to use certain protection mechanisms to keep pace with large companies and technological precursors in fast growing markets.
urn:nbn:de:0011-n-1021723
Keywords: 330; patents; secrecy; expected utility; Intellectual property; rational choice; Intangibles Gut; Immaterialgüterrechte; Patent; Geschäftsgeheimnis; Erwartungsnutzen; Großunternehmen; Klein- und Mittelunternehmen; Deutschland